3(4x+2)+39=15x+3-3x+42

Simple and best practice solution for 3(4x+2)+39=15x+3-3x+42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+2)+39=15x+3-3x+42 equation:



3(4x+2)+39=15x+3-3x+42
We move all terms to the left:
3(4x+2)+39-(15x+3-3x+42)=0
We add all the numbers together, and all the variables
3(4x+2)-(12x+45)+39=0
We multiply parentheses
12x-(12x+45)+6+39=0
We get rid of parentheses
12x-12x-45+6+39=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 4+-p=-2 | | s+95=–4 | | 30–2(10–3x)=4x+3(3x–20) | | 10*(10x-8)-5*(6x-2)=0 | | 16x232=360 | | v+22=3v | | 22=9-7x | | t-5.9=10.94 | | b+15=6b | | 10x–7=4x−31 | | 8*(6x+11)+12*(9x-6)=-140 | | 4-2r=-4 | | 7238-3478=94(77x-37) | | 5x-2.7=-7x-7.1 | | x=2(3.14)2 | | -5.2(m+3.4)=2.6 | | (4x+12)2x=180 | | 4(x-2)-9=6x-2(5+x) | | -9+3d=0 | | 9a+6a-23+12=0 | | x2+x−110=0 | | 10x-7=4x-31 | | (36+x)/(9+x)=16/7 | | 4(h+12)=6 | | 4(2m-1)=2m+35 | | 2x(-x^2+6)=0 | | 6(h+12)=4 | | 2(4x-2)-3x=12+5x-9 | | 2a-8+4a=0 | | 3/5a-4=2/5a | | 3.14=2(3.14)x | | 2w^2-10=0 |

Equations solver categories